Interprofessional Education in Nursing as a Strategy to Enhance Healthcare Team Collaboration - Al-bahra Al-Bahra; Hardjito S. Darmojo (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2025)
Interprofessional education (IPE) is a learning approach that involves students from various health professions to learn together, understand each other's roles, and develop collaborative skills in healthcare. This approach is increasingly important in nursing education given the complexity of patient needs and the demands of effective collaborative healthcare team practices. This study aims to analyze the role of interprofessional education in nursing as a strategy to improve healthcare team collaboration. The research method used a quantitative approach with a quasi-experimental design, involving nursing students and other healthcare professionals participating in an interprofessional education program based on case discussions and clinical simulations. Healthcare team collaboration was measured using a standardized instrument that assesses communication, role understanding, teamwork, and shared decision-making. The results showed a significant increase in healthcare team collaboration skills after the interprofessional education intervention. The most prominent improvements were seen in interprofessional communication and understanding of professional roles. These findings confirm that interprofessional education is an effective learning strategy for preparing nursing students for collaborative practice in healthcare settings. The systematic integration of interprofessional education into the nursing curriculum is recommended to improve the quality of care and patient safety.